2016
DOI: 10.1371/journal.pone.0151430
|View full text |Cite
|
Sign up to set email alerts
|

Interference and Inhibition in Bilingual Language Comprehension: Evidence from Polish-English Interlingual Homographs

Abstract: The main goal of the present study was to explore the involvement of inhibition in resolution of cross-language activation in bilingual comprehension and a possible modulatory effect of L2 proficiency. We used a semantic relatedness judgment task in L2 English that included Polish-English interlingual homographs and English translations of the Polish homographs’ meanings. Based on previous studies using the same paradigm, we expected a strong homograph interference and inhibition of the homographs’ Polish mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 34 publications
(58 reference statements)
2
30
1
3
Order By: Relevance
“…In the current study, we did not find behavioral differences between the homophone-related and homophone-unrelated conditions, which contrasts with bilingual visual word studies in which behavioral differences were observed (Durlik et al, 2016; Macizo et al, 2010; Martín et al, 2010). The current study constructed homophone word pairs in a very similar way to these behavioral studies (homophones with auditory presentation vs. homographs with visual presentation); therefore, a similar pattern of behavioral results was expected.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In the current study, we did not find behavioral differences between the homophone-related and homophone-unrelated conditions, which contrasts with bilingual visual word studies in which behavioral differences were observed (Durlik et al, 2016; Macizo et al, 2010; Martín et al, 2010). The current study constructed homophone word pairs in a very similar way to these behavioral studies (homophones with auditory presentation vs. homographs with visual presentation); therefore, a similar pattern of behavioral results was expected.…”
Section: Discussioncontrasting
confidence: 99%
“…This unexpected finding could be due to differences in simultaneous and sequential presentation across visual and auditory modalities. During the simultaneous presentation, bilinguals may have experienced difficulty resolving the interference because the source of the interference – homographs – was constantly shown on the screen before a decision was made (Durlik et al, 2016; Macizo et al, 2010; Martín et al, 2010). In the sequential presentation, the interval between the two words provided a buffering zone that made semantic interference manageable; therefore, no conflicts were detected by behavioral measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations